ANALISIS LITERASI NUMERASI PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN NILAI MUTLAK LINEAR SATU VARIABEL DIKAJI DARI KECERDASAN EMOSIONAL - Esa Sandi Putri; Edy Yusmin; Asep Nursangaji (Jurnal AlphaEuclidEdu, 2021)
This study aims to determine numeracy literacy in the material equations and inequalities of the absolute value assessed from the emotional intelligence of students at SMA Panca Setya Sintang. The method used in this research is descriptive with a case study research. The subjects in this study were students of grade X IPA 3 with a total of 17 students. The object to be researched is numeracy literacy in the material equations and inequality of the absolute linear value of one variable assessed from the emotional intelligence of students. The techniques used in data collection are questionnaires, numeracy literacy tests and interviews. The results obtained from this study that there were four students who had high levels of emotional intelligence and tended to have high numeracy literacy, eleven students had moderate emotional intelligence and also varied numeracy literacy with one student with good numeracy literacy, six students with good numeracy and four students with poor numeracy, and two students who had low levels of emotional intelligence and had low numeracy literacy. Keywords: Numeracy Literacy, Emotional Intelligence, Equations And Inequalities Of The Absolute Value